Smart mobility as sustainable mobility: Application to the agglomeration of Fez in Morocco - Mohammed Mouhcine MAAROUFI; Laila STOUR; Ali AGOUMI (Smart Cities and Regional Development Journal)
To be sustainable, mobility must be smart, safe, fair, and take into account the harmful effects on the environment. It must improve the quality of citizen’s life by safeguarding human health and natural ecosystems. This sustainable mobility must optimize resource consumption and public spaces, facilitate accessibility, promote economic dynamism, commit to the social responsibility of individuals, companies, and society, and respect environmental integrity [1]. Thus, sustainable mobility contributes to development and responds to the travel demands of present generations without compromising the ability of future generations to meet their own needs [2]. All modes of transport emitted in Morocco in 2014: 16 million tons of CO2 equivalent representing 19.2% of the country's total emissions. Morocco has set itself a target of 42% for reducing GHG emissions from the year 2030 [3]. This article presents the results of research conducted for the setting up of a new model of sustainable mobility - in a horizon of 20 years – in an urban Moroccan area, booming 'Fez'. It offers a conceptual approach to measuring the sustainability of the transport system. An analysis of the supply and the need for trips in a reference situation first allows for formalizing realistic objectives. Then, a sustainable mobility model is developed to prevent social and environmental costs from being higher than the services provided by the transport systems of this city. Finally, a comparison between the trend situation and the corrected situation with this sustainable mobility model allows us to appreciate its contribution.